Examining The Doctrine of Seven Grades of Being (Maratib Sab’ah) in Tuhfah al-Mursalah; An overview toward Quranic’s Perpective - AB, Zuherni; Juwaini, Juwaini (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
The seven grades (Marataib al-Sab’ah) very closed associated with Muhammad Fadhl Allah al-Burhanpuri, an Indian Sufi scholar through his Tuhfah al-Mursalah ila Ruh al-Nabi. Written di Arabic Tuhfah al-Mursalah’s circled around India and also popularize in Mecca Madina and Malay word afterward.  Burhanpuri and Tuhfah al-Mursalah many times mention in numerous manuscripts written in Arab Jawi, which identified from his principles mostly from ‘alam jawi (Nusantara) around 16-17 century. Some of them Shams al-Din al-Sumatra’i, Hamzah al-Fansuri, Nur al-Din al-Raniry and ‘Abd al-Ra’uf al-Singkili. Afterward, these principles, identically Maratib al-Sab’ah in Malay world known as Martabat Tujuh. The main point suggested by Burhanpuri, an explaration toward Ibn ‘Arabi’s idea wahdah al-wujud. Maratib al-Sab’ah considered as the proper medium to attain Ibn ‘Arabi’s Oneness of Being and relate it with the Qur’an perspective and as well as Hadits point of view on certain explanation in his Tuhfah al-Mursalah.